Adaptation to Income over Time: A Weak Point of Subjective Well-Being - Christoph Wunder (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
This article holds the view that intertemporal comparisons of subjective well-being measures are only meaningful when the underlying standards of judgment are unaltered. This is a weak point of such measures. The study investigates the change in the satisfaction judgments resulting from adaptation to income over time. Adaptation is defined to be desensitization (sensitization) to the hedonic effect of income resulting from an upward (downward) adjustment of the standards. A framework is introduced that provides empirical estimates for the rate of adaptation using data from the Socio-Economic Panel Study (SOEP).
Keywords: C23; I31; 330; Adaptation; financial satisfaction; subjective well-being; standards of judgment